Pelatihan Pembelajaran Model Tematik Integratif Nilai-nilai Pancasila dengan sintak HAJRAH bagi Guru Taman Kanak-kanak di Kecamatan Gantarang Kabupaten Bulukumba - Hajerah, Hajerah; Intisari, Intisari; Amri, Nur Alim; Sadaruddin, Sadaruddin; Usman, Usman (LP2M Universitas Muhammadiyah Enrekang, 2024)
The integrative thematic learning model of Pancasila values with HAJRAH syntax is a learning model designed to stimulate children's abilities, one of which is Pancasila values using syntax: high preparation, action, joining, reaction, assement, high reinforcement (HAJRAH). For teachers, this learning model is needed based on objective conditions in the field related to the scope of implementation of the integrative thematic learning model of Pancasila values in learning the new paradigm curriculum in kindergartens in driving schools. This activity was carried out in Gantang District, Bulukumba Regency which aims to provide education to teachers so that they can use various learning models that suit current needs, one of which is the integrative thematic learning model of Pancasila values with HAJRAH syntax. The methods used are varied lecture methods, practices and demonstrations in identifying, developing and compiling as well as how to apply this model to the learning process. The result of this activity is that teachers can apply the integrative thematic learning model of Pancasila values with HAJRAH syntax based on environment-based themes and topics.